International Financial Assistance and Inequality in Emerging Markets: Colombia, Egypt and Turkey - Farag, Sara (AUC Knowledge Fountain, 2022)
This research study investigates the effects of the three main pillars of structural adjustment policies imbedded in IFI funding facilities on income inequality in three specific cases; Colombia, Egypt and Turkey to uncover if income inequality present in those emerging markets is attributed to; the policy reforms conditionality or to pre-existent country features. The three main pillars of policy conditions discussed in this thesis are 1. Government Expenditure Reforms, 2. External Sector Reforms, and 3. Financial Sector Reforms. My hypothesis is that, although pre-existent country features may have had an impact on the levels of inequality a populace faces, the role of funding assistance sponsored by the IMF will act as a significant catalyst deteriorating the conditions that are already in place. Out of the three main policy pillars I hypothesise that government expenditure reforms and financial sector reforms will have the most significant impact on income distribution, as they are the two pillars that are most likely to directly impact the poorest segments of the populace. My findings suggest that the neo-liberal structural reform policies that the IMF imposed upon the chosen emerging markets had an overall negative impact on income equality, as evident in the Colombian and Egyptian case. The Turkish case also reinforced this conclusion since, as the Turkish government abstained from implementing one of the main three pillars of conditionality, the levels of income inequality in the country improved on the longer run.